Emotional intelligence as predictor of resilience toward academic stress mitigation among Public and Private Medical College students - Murtaza Maqbool Khan Bhati, Javeria Ghafoor, Muhammad Immran, Tayyeba Idrees Butt, Sundas Ahmad, Mavra Imtiaz (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Emotional intelligence is a crucial concept in management, business, engineering, nursing and medicine. It has gained more attention than personality and Intelligence Quotient. Understanding human emotions is essential for understanding emotional intelligence. Aim: High-EQ individuals can combine intellectual and emotional skills to adapt to new situations and achieve goals. Individuals with high emotional intelligence can read interpersonal cues and manipulate others’ emotions. Method: The Comparative study is conducted in Rai Medical College Sargodha from April 2021 to August 2022and population was the MBSS students. Provide more demographic and socioeconomic data on survey participants. Determine the emotional intelligence traits all respondents share. Determine the respondents’ academic achievement and calculate an average. Thoroughly study how socioeconomic background affects emotional intelligence. Determine if respondents’ socioeconomic profile affects academic performance. To examine and publish the relationship between emotional intelligence components and respondents’ academic performance. Result: The study reveals a significant correlation between gender and emotional intelligence, with women generally having greater emotional intelligence. The majority of respondents are male, with 97.14% attending public institutions and 2.5% attending private medical colleges. Age and educational degree also impact emotional intelligence, with 54.89% of respondents aged 18-19 and 36.73% aged 20-22. Higher education levels are associated with increased emotional intelligence. Conclusion: Emotional intelligence and academic performance were positively correlated. Emotional regulation and adaptive emotions are linked, suggesting emotional intelligence may prevent ASD. The study shows that high-AR students naturally manage and use emotional information to perform better academically. This supports the COR-based theoretical claims linking AR, EI, and AP. Keywords: Emotional intelligence, Stress, Behavioral science, Public Private medical college.